2009
DOI: 10.1117/1.3120494
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared narrow-band imaging of gold/silica nanoshells in tumors

Abstract: Gold nanoshells (GNS) are a new class of nanoparticles that can be optically tuned to scatter or absorb light from the near-ultraviolet to near-infrared (NIR) region by varying the core (dielectric silica)/shell (gold) ratio. In addition to spectral tunability, GNS are inert and bioconjugatable, making them potential labels for in vivo imaging and therapy of tumors. We report the use of GNS as exogenous contrast agents for enhanced visualization of tumors using narrow-band imaging (NBI). NBI takes advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…27,28 Recently, we demonstrated that systemically delivered GNSs passively accumulated in human colon tumors and served as excellent absorption-based contrast agents for wide-field tumor imaging. 29 Smaller particles have high permeation/diffusion through tumor interstitium and correspondingly, higher clearance to surrounding normal tissue (where they are likely to be cleared). 30 Jain et al and Boucher et al have shown that the interstitial fluid pressure decreases from the tumor core to the periphery and surrounding tissue, carrying nanoparticles with it by convection into the normal tissue as a function of particle size.…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Recently, we demonstrated that systemically delivered GNSs passively accumulated in human colon tumors and served as excellent absorption-based contrast agents for wide-field tumor imaging. 29 Smaller particles have high permeation/diffusion through tumor interstitium and correspondingly, higher clearance to surrounding normal tissue (where they are likely to be cleared). 30 Jain et al and Boucher et al have shown that the interstitial fluid pressure decreases from the tumor core to the periphery and surrounding tissue, carrying nanoparticles with it by convection into the normal tissue as a function of particle size.…”
Section: Discussionmentioning
confidence: 99%
“…69 It is assumed that based on the EPR effect, small nanoparticles (,400 nm), including nanoshells, selectively accumulate in the tumor tissue by the passive extravasation associated with the leaky tumor vascularity. 28,30,69 In theory, upon accumulation within tumors, nanoshells interfere in cell damage and aid in cancer/tumor treatment by absorbing NIR light and transforming it into heat as a result of their plasmonic characteristics. When using nanoshells that are designed to be scatterers (higher scattering cross-sections), cancerous cells could be detected even at an early stage.…”
Section: Photothermal Ablationmentioning
confidence: 99%
“…24 Larger nanoparticles instead demonstrate larger scattering crosssections 25 that can be exploited for contrast enhancement in bioimaging. [26][27][28][29] The resonant excitation of larger particles though, when of 100 nm or over in size, shows significant contributions from higher order multipole modes that create a broader far-field extinction spectra. The combination of the absorption and scattering properties, which depends on the size of the particle, allows nanoparticle-based integrated diagnostic imaging and therapy.…”
Section: Introductionmentioning
confidence: 99%
“…However, the SiO 2 /Au particles are unstable in physiological environments, so their stabilities need to be increased for in vivo applications. As a result of the steric stabilization and stealth properties of poly(ethylene glycol) (PEG), PEGylation of SiO 2 /Au hybrid nanoparticles is widely used to make the particles suitable for in vivo applications [19][20][21]. However, PEGylation of nanoparticles by mono-endfunctionalized PEG often causes de-PEGylation under physiological conditions [22], resulting in aggregation of the particles.…”
Section: Introductionmentioning
confidence: 99%